Associations between conflicting nutrition information, nutrition confusion and backlash among consumers in the UK. Issue 5 (12th April 2021) - Vijaykumar, Santosh; McNeill, Andrew; Simpson, Joshua
Abstract: Objective: To examine the effects of exposure to conflicting nutritional information (CNI) through different forms of media on nutrition-related confusion and backlash among consumers in the UK. Design: Cross-sectional survey administered via Qualtrics among 18–75-year-old participants in the UK. The sample was stratified by age and gender with quotas defined according to the 2011 UK census distribution. Setting: Qualtrics' Online panel of respondents in the UK. Participants: 676 participants comprising nearly an equal number of females ( n 341) and males ( n 335) and a majority (58·6 %) from households whose income was <£30 000. Results: Our findings showed that nearly 40 % of respondents were exposed to some or a lot of CNI. We found that while exposure to CNI from TV and online news increased nutrition confusion, CNI from health professionals increased backlash. Exposure to CNI from social media and health websites was associated with reduced backlash. We also found that nutrition confusion and backlash were negatively associated with exercise behaviour and fruit and vegetable consumption, respectively. Conclusions: Our study supports the theoretical pathways that explain the influence of CNI exposure on nutrition-related cognitive and behavioural outcomes. Additionally, different types of online information sources are associated with these outcomes to varying degrees. In the context of obesity and diabetes rates in the UK, our findings call for (a) further experimental research into the effects of CNI on consumers' diet-related cognitions and behaviours and (b) multi-stakeholder, interdisciplinary approaches to address this problem.